The expression and role of Lysyl oxidase (LOX) in dentinogenesis. (28th November 2012) - Tjäderhane, L.; Vered, M.; Pääkkönen, V.; Peteri, A.; Mäki, J. M.; Myllyharju, J.; Dayan, D.; Salo, T.
Abstract Aim To establish whether eliminating Lysyl oxidase (LOX) gene would affect dentine formation. Methodology Newborn wild‐type (wt) and homo‐ and heterozygous LOX knock‐out (Lox−/− and Lox+/−, respectively) mice were used to study developing tooth morphology and dentine formation. Collagen aggregation in the developing dentine was examined histochemically with picrosirius red (PSR) staining followed by polarized microscopy. Because Lox−/− die at birth, adult wt and Lox+/− mouse tooth morphologies were examined with FESEM. Human odontoblasts and pulp tissue were used to study the expression of LOX and its isoenzymes with Affymetrix cDNA microarray. Results No differences between Lox−/−, Lox+/− and wt mice developing tooth morphology were seen by light microscopy. Histochemically, however, teeth in wt mice demonstrated yellow‐orange and orange‐red polarization colours with PSR staining, indicating thick and more densely packed collagen fibres, whilst in Lox−/− and Lox+/− mice, most of the polarization colours were green to green‐yellow, indicating thinner, less aggregated collagen fibres. Fully developed teeth did not show any differences between Lox+/− and wt mice with FESEM. Human odontoblasts expressed LOX and three of four of its isoenzymes. Conclusions The data indicate that LOX is not essential in dentinogenesis, even though LOX deletion may affect dentine matrix collagen thickness and packing. The absence of functional LOX may be compensated by LOX isoenzymes.